Moderasi Dukungan Pemerintah dan Mediasi Perubahan Strategis Terhadap Kinerja UMKM - Nur Fitriana; Siti Rodiah; Rara Nagita; Olitsha Amanda; Imelia Sari (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research tries to see the influence of the availability of financial capital, innovative work behavior, strategic changes, and government support on the performance of MSMEs Methodology/approach: Using mediation and moderation models, this research tries to examine the relationship between these variables. The research method used was a quantitative approach with 100 respondents from MSMEs in Riau Province taken using a cluster random sampling technique. The research analysis technique uses path analysis using the Smart PLS tool which aims to look at the outer model, inner model and hypothesis testing. Findings: this research succeeded in proving that government support can strengthen the relationship between the availability of financial capital, innovative performance behavior and strategic changes to the performance of MSMEs. However, this research has not been able to prove the direct influence of innovative performance behavior and the indirect influence of strategic changes on the performance of MSMEs Practical implications: The results of this research have an impact on the importance of government support in MSME finance. The government is expected to pay more attention to MSMEs' needs for sufficient and stable finance. Originality/value: There are still limited research references regarding the availability of financial capital, innovative work behavior, and the performance of MSMEs mediated by strategic change and moderated by government support. This research develops previous research which is modified in the mediation and moderation model